2017
DOI: 10.1002/lary.26615
|View full text |Cite
|
Sign up to set email alerts
|

Laryngectomy and smoking: An analysis of postoperative risk

Abstract: 4. Laryngoscope, 127:2302-2309, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Although some series have shown that smoking is associated with higher rates of surgical and medical complications, 27,28 other studies regarding head and neck surgical resection and free-flap reconstruction have not found smoking to be a significant independent predictor of surgical complications. 15,29 Last, prior disease or receipt of RT were not found to significantly increase the risk of overall or wound complications on univariate analysis or in multivariate models, which other studies similarly have found. 30,31 Multivariate analysis of LOS demonstrated that only UADT surgery, compared with cutaneous surgery, was an independent predictor.…”
Section: Discussionmentioning
confidence: 58%
“…Although some series have shown that smoking is associated with higher rates of surgical and medical complications, 27,28 other studies regarding head and neck surgical resection and free-flap reconstruction have not found smoking to be a significant independent predictor of surgical complications. 15,29 Last, prior disease or receipt of RT were not found to significantly increase the risk of overall or wound complications on univariate analysis or in multivariate models, which other studies similarly have found. 30,31 Multivariate analysis of LOS demonstrated that only UADT surgery, compared with cutaneous surgery, was an independent predictor.…”
Section: Discussionmentioning
confidence: 58%
“…These results stand in contrast to previous studies that have shown a significant association between smoking and postoperative pulmonary and neurological complications . In a recent study of patients undergoing laryngectomy, Brady et al also found no increase in overall morbidity attributable to smoking. These authors suggested that the prior literature may have failed to correct for the number of comorbidities associated with smoking, including differences in the extent of disease, which may artificially inflate the risk associated with tobacco smoke.…”
Section: Discussionmentioning
confidence: 99%
“…Given that smoking status is associated with worse surgical outcomes, head and neck surgeons should have the option to delay operating until smoking cessation is achieved. [4][5][6][7] Continued smoking during adjuvant radiation therapy is further associated with a decreased therapy response and lower rates of survival. 14 Compelling surgeons to operate without taking these risks into account undermines their professional judgment to act in the patient's best interests and can increase their moral distress if they believe that immediate surgery constitutes unnecessarily suboptimal care.…”
Section: Respecting Professional Judgmentmentioning
confidence: 99%
“…4 Smoking is also a risk factor for surgical site infections in patients with head and neck cancer. 5 Brady et al 6 report increased rates of postoperative pneumonia, sepsis, and medical complications in smokers with more than 50 pack-years. In addition, patients who smoke have more frequent flap necrosis, with 83% of paramedian forehead and nasolabial flap failures occurring in this population.…”
Section: Reducing Postoperative Complicationsmentioning
confidence: 99%